1973
DOI: 10.1104/pp.51.4.677
|View full text |Cite
|
Sign up to set email alerts
|

The Genes for Cytoplasmic Ribosomal Ribonucleic Acid in Higher Plants

Abstract: The genes for cytoplasmic ribosomal RNA are partially resolved from the bulk of the DNA by CsCI equilibrium centrifugation. Although in some plants the buoyant density of the ribosomal RNA genes is as expected from the base composition of ribosomal RNA, others show a large discrepancy which cannot be due to the presence of low G-C spacer-DNA. The crosshybridization observed with 1.3 and 0.7 X 100 molecular weight ribosomal RNAs and DNA, which varies greatly with different plant species, is not due to contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 28 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…It has been shown that the extent of hybridisation depends on whether the 13 x 10° daltons rRNA or the 07 x 106 daltons rRNA are used (Scott and Ingle, 1973;Cullis, 1975). For the comparison of the various lines here a 2: 1 mixture of the two rRNAs was used as this gave essentially the same relative values as those obtained for the 13 x 106 daltons rRNA alone (Cullis, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the extent of hybridisation depends on whether the 13 x 10° daltons rRNA or the 07 x 106 daltons rRNA are used (Scott and Ingle, 1973;Cullis, 1975). For the comparison of the various lines here a 2: 1 mixture of the two rRNAs was used as this gave essentially the same relative values as those obtained for the 13 x 106 daltons rRNA alone (Cullis, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The main band had a calculated value of 1.691 g/ml and they noticed two satellites at 1.696 and at 1.705 g/ml. INGLE et al (1973) found the values of 1.693, 1.692 and 1.694 g/ml for the main bands of coccineus, vulgaris and aureus respectively. The heavy satellite was 1.702, 1.703 and 1.705 in these same species respectively.…”
Section: The Buoyant Density Of the Dna Satellitesmentioning
confidence: 91%
“…Other large satellites are present in Cucumis safivus (28 %), in C. melo (25 %) and in citrus species (24 to 19 %, INGLE et al 1973).…”
Section: Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…DNA was extracted from the methanogen after disruption in a French Pressure Cell by the method of Scott and Ingle [11]. The guanine+ cytosine (G + C) content was estimated from buoyant density measurements by CsCI equilibrium density centrifugation using an MSE centriscan 75 centrifuge.…”
Section: Guanine + Cytosine Determinationmentioning
confidence: 99%